2020
DOI: 10.3892/ol.2020.11278
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial genes and pathways associated with colorectal cancer by bioinformatics analysis

Abstract: Colorectal cancer (CRC) is a prevalent malignant tumour type arising from the colon and rectum. The present study aimed to explore the molecular mechanisms of the development and progression of CRC. Initially, differentially expressed genes (DEGs) between CRC tissues and corresponding non-cancerous tissues were obtained by analysing the GSE15781 microarray dataset. The Database for Annotation, Visualization and Integrated Discovery was then utilized for functional and pathway enrichment analysis of the DEGs. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Excessive expression of IL-6 is the most common finding when investigating the association of inflammation and cancer. IL-6 regulates numerous signaling pathways, including apoptosis, survival, proliferation, angiogenesis, invasion, and metastasis [ 11 13 ]. In a number of studies, IL-6 acts as a protector of cancer cells from therapy-induced DNA damage, oxidative stress, and apoptosis, contributing to repair [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive expression of IL-6 is the most common finding when investigating the association of inflammation and cancer. IL-6 regulates numerous signaling pathways, including apoptosis, survival, proliferation, angiogenesis, invasion, and metastasis [ 11 13 ]. In a number of studies, IL-6 acts as a protector of cancer cells from therapy-induced DNA damage, oxidative stress, and apoptosis, contributing to repair [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 plays a crucial role in regulating lipid metabolism and adipocyte differentiation associated with the tumor suppressor, PTEN [ 34 ]. FABP4 and ADIPOQ have been reported to increase the risk of colorectal neoplasia related to the COAD survival probability [ 35 , 36 ]. Dudgeon et al found that UCN can inhibit COAD cell growth via inducing apoptosis by PUMA and a p53 target [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ribonucleotide reductase regulatory subunit m2 ( RRM2 ) gene, which is a part of the cell cycle and p53 signaling pathway, is also known to be overexpressed in CRC [ 18 ], and has been correlated with the poorly differentiated type, invasion depth, and tumor node metastasis stages in CRC [ 18 ]. Among the other cell cycle and p53 signaling pathway genes are DNA topoisomerase 2-alpha ( TOP2A ) [ 58 ], cell division cycle 6 ( CDC6 ) [ 59 , 60 ], nucleolar and spindle associated protein 1 ( NUSAP1 ) [ 61 ], centrosomal protein 55 ( CEP55 ) [ 62 ], budding uninhibited by benzimidazoles 1 ( BUB1 ) [ 63 ], and the mitotic arrest deficient 2 like 1 ( MAD2L1 ) [ 63 ], which are known to be differentially expressed in CRC, and are related to the aggressive tumor phenotypes and advanced tumor stages.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%
“…Apart from the genes associated with stress survival pathways, genes encoding for different kinases have also been seen to be differentially expressed in various CRC cases. The top candidates include serine/threonine-protein kinase ( PLK1 ) [ 19 , 103 ], aurora kinase A ( AURKA ) [ 63 ], checkpoint kinase 1 ( CHEK1 ) [ 78 ], and maternal embryonic leucine zipper kinase ( MELK ) [ 100 ]. These genes are seen to control the proliferation, migration, invasion of CRC cells, prognosis, or metastasis of CRC.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%